Basic and Advanced Skills They Don’t Have: The Case of Postgraduate and Literature Review Writing (Malaysian Journal of Learning and Instruction, 2015)
Purpose â€“ This paper aims to identify the difficulties postgraduate students face in writing the literature review for their thesis and dissertation. Methodology â€“ Seventy postgraduate students from 9 faculties in one public university in the Klang Valley consented to participating in this study. They were 49 Masters candidates and 21 doctoral (PhD) candidates attending a workshop on academic writing. Among them, 31 were Malaysians and 39 were foreigners with majority being Arabs and Africans. After an icebreaking session, participants were asked what their writing diffi culties are when doing their literature review. They were told to write their responses in English in a paper. A linguistic analysis was then applied to the written phrases and expressions which denote their diffi culties. These were then categorised under common themes and manually counted in terms of the frequency. Findings â€“ A total of 37 categories of diffi culties were detected. They encompassed basic and advanced skills in reading and writing including â€˜not knowing what to readâ€™, â€˜how to readâ€™, â€˜how to start writingâ€™, â€˜organisingâ€™, â€˜doing a critical analysisâ€™, â€˜summarisingâ€™ and â€˜synthesisingâ€™. Significance â€“ The fi ndings imply that most of the participants do not possess the necessary skills of reading and writing which are required in most postgraduate programmes. Thus, it is imperative that institutions of higher learning develop stricter criteria for student selection. Alternatively, a programme providing support in reading and writing may enable these postgraduate students to raise their level before being admitted. This kind of support can help to mitigate the burden imposed on supervisors as well as develop better quality postgraduate students.